Increasing Students’ Psychological Well-Being and Academic Resilience Through Cognitive-Behavioral Intervention and Mindfulness Relaxation Integrated with Islamic Values - Sri Wahyuni; Munthe, Ricca Angreini; Sakia Eka Fadilla (Psikis : Jurnal Psikologi Islami, 2024)
Psychological well-being and academic resilience are crucial factors for students' success in higher education, contributing to both academic achievement and mental health. Therefore, it is essential to implement strategies aimed at enhancing students' psychological well-being and academic resilience. This study aimed to evaluate the effectiveness of a cognitive-behavioral intervention and mindfulness relaxation integrated with Islamic values in improving students' psychological well-being and academic resilience. The research employed a mixed-methods approach. The quantitative component utilized an experimental design, specifically a non-equivalent control group design. The research subjects were divided into four groups, with a total of 70 participants. The instruments used for measurement including the Psychological Well-being Scale (α = 0.897) and the Academic Resilience Scale (α = 0.884). Data analysis was conducted using multivariate analysis of variance. In addition to the quantitative analysis, the qualitative method explored participants' feelings before and after the intervention. The study found no significant effect of the cognitive-behavioral intervention and mindfulness relaxation integrated with Islamic values on increasing psychological well-being and academic resilience across all experimental groups. However, qualitative data revealed that the intervention had a positive impact on students' psychological well-being and academic resilience. Overall, while the quantitative results did not show significant improvements, the qualitative feedback suggests that the intervention may still hold value in supporting students' mental health and resilience.